Successional pattern of phytoplankton (>55μm) in Lekki lagoon, Nigeria - Abosede Adesalu, Taofikat (2012)
Lagoons are dominant features along large stretches of the West Africa coast. These freshwater environments are very valuable areas where phytoplankton constitute the basis of aquatic food webs. In order to know the effects of environmental variables on phytoplankton, a study of the successional pattern of phyto- plankton in Lekki lagoon was carried out monthly for two years (June 2003-May 2005). Phytoplankton samples were collected from 12 stations using a plankton net of 55μm mesh, and samples preserved in 4% unbuffered formalin. Besides, surface water samples were taken for physico-chemical analysis. For each year, the seasonal distribution and succession of dominant phytoplankton followed different patterns. Phytoplankton abundance was higher during the dry season (November-April) for the two annual cycles. The diatoms (Aulacoseira granulata and A. granulata var angustissima) and blue green algaes, Microcystis aeruginosa, Merismopedia tennuissima and Trichodesmium lacustre showed this trend by being the abundant species in some of these months. For the rainy season, the green alga Mougeotia sp. dominated. The replacement of one form by another throughout seasonal cycles was probably controlled by the changes in environmental variables such as rainfall, nitrate- nitrogen and phosphate-phosphorus.